2012
DOI: 10.2166/wst.2012.847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a moving bed bioreactor and a fixed bed bioreactor for biological phosphate removal and denitrification

Abstract: Moving bed bioreactors (MBBR) and fixed bed bioreactors (FBBR) were compared for biological phosphorus removal and denitrification. The sorption denitrification P-elimination (S-DN-P) process was selected for this study. Results indicated that all nutrients were removed by the FBBR process compared with the MBBR process: 19.8% (total COD), 35.5% (filtered COD), 27.6% (BOD(5)), 62.2% (acetate), 78.5% (PO(4)-P), and 54.2% (NO(3)-N) in MBBR; 49.7% (total COD), 54.0% (filtered COD), 63.2% (BOD(5)), 99.6% (acetate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Valderramna et al [22] obtained 71.6 % TN removal by C. vulgaris in the treatment of industrial wastewater. Choi et al [21] found 76.8 % TN removal under fixed bed MBR operated for domestic wastewater.…”
Section: Tn No 3 -N and Nh 4 -N Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Valderramna et al [22] obtained 71.6 % TN removal by C. vulgaris in the treatment of industrial wastewater. Choi et al [21] found 76.8 % TN removal under fixed bed MBR operated for domestic wastewater.…”
Section: Tn No 3 -N and Nh 4 -N Removalmentioning
confidence: 99%
“…Various nitrogen removal techniques were demonstrated in aquaculture systems that can either remove or convert one form of nitrogen to another [21]. The removal of TN, NO 3 -N, and NH 4 -N by MMBR was shown in Fig.…”
Section: Tn No 3 -N and Nh 4 -N Removalmentioning
confidence: 99%
“…The study of Choi et al . () would help determine the practical significance of MBBR and FBBR removal of bio‐P and denitrification from wastewater. They indicated that the amount of all nutrients (total COD, filtered COD, BOD 5 , acetate, PO 4 ‐P, NO 3 ‐N) removed by FBBRs was higher than that removed by MBBR.…”
Section: Biological Filtration Equipmentmentioning
confidence: 99%
“…As with any technical language, aquaponics has definitions that are domain‐specific and sometimes not very precise. For example, bioreactor and its subcategory ‘moving bed bioreactor’ 77 which provide the habitat for nitrifying bacteria are often called biofilter in aquaponic context, even though nothing is filtered out here. Rather than that, chemical compounds are altered and bacterial biomass is built up—the transformation of fish‐toxic ammonia and ammonium over nitrite to nitrate by nitrifying bacteria 12 .…”
Section: Concerning Some Aquaponic Termsmentioning
confidence: 99%